A molecular epidemiological perspective of rhinovirus types circulating in Amsterdam from 2007 to 2012. (December 2016) - van der Linden, L.; Bruning, A.H.L.; Thomas, X.V.; Minnaar, R.P.; Rebers, S.P.H.; Schinkel, J.; de Jong, M.D.; Pajkrt, D.; Wolthers, K.C.
Abstract: Rhinoviruses (RVs) are frequently detected respiratory viruses that cause mild common cold symptoms, but may also lead to more severe respiratory tract infections. The large number of RV types, classified into species A, B and C, hampers clear insights into the epidemiology and clinical significance of each RV type. The aim of this study was to map the circulation of RV types in the Amsterdam area. RV-positive nasopharyngeal and oropharyngeal samples, collected from 2007 to 2012 in the Academic Medical Centre (Amsterdam, the Netherlands), were typed based on the sequence of the region coding for capsid proteins VP4 and VP2. RV-A, RV-B and RV-C were found in proportions of of 52.4% (334/637), 11.3% (72/637), and 36.2% (231/637), respectively. We detected 129 of the 167 currently classified types. RVs circulated throughout the entire year with a peak in the autumn and a decline in the summer. Some RV types were observed throughout the entire sampling period and others had a more seasonal pattern. Nine RV-A and four RV-B novel provisionally assigned types were identified. This study provides an insight into the molecular epidemiology of RVs in the Amsterdam area. The RVs circulating are diverse and include several provisionally new types.